Conceptions and practices for rooting in the educational centers to total production - Miano, María Amalia (Emerging Trends in Education, 2024)
Rooting is postulated as a category to analyze the conceptions and practices that occur within the framework of the Educational Centers for Total Production (rural alternative secondary schools in the province of Buenos Aires, Argentina) to achieve the permanence of students and their families in rural areas. There are two dimensions of rootedness: that linked to the emotional disposition in relation to the environment and that which involves collective actions to improve living conditions. Methodologically, data generated in field work started in 2016, carried out with a collaborative ethnographic approach, was analyzed. The analysis was carried out by creating emerging categories highlighting the positions of the various actors that participate in these Educational Centers (families, students, officials participated in the opening of these Centers). It is argued that, by establishing roots as an objective that exceeds education, these Educational Centers achieve the permanence of rural families through the development of productive projects and strategies for access to land. In this way, through articulation with an educational institution such as the CEPT, dynamics linked to the enclosure and expulsion of rural families are managed.
Keywords: Alternation; Rural rootedness; High school education; Community participation; Rural population